Senyawa Hidrazone dari Vanilin-DNPH Sebagai Sensor Kolorimetri Anion Sianida - S Suharman; Siti Utari Rahayu (UNIVERSITAS SEBELAS MARET (UNS), 2020)
Senyawa hidrazon (E)-4-((2-(2,4-dinitrophenyl)hydrazineylidene)methyl)-2-methoxyphenol telah disintesis dari vanilin dan 2,4-dinitrofenilhidrazin (DNPH). Uji sensor anion dilakukan dengan menambahkan anion F-, Cl-, Br-, I-, CN-, SO42-, CO32-, CH3COO- dan H2PO4- dalam pelarut asetonitril. Uji limit deteksi reseptor (E)-4-((2-(2,4-dinitrophenyl)hydrazineylidene)methyl)-2-methoxyphenol terhadap anion sianida dilakukan dalam pelarut asetonitril. Hasil uji sensor anion menunjukan bahwa reseptor selektif terhadap anion sianida dengan menghasilkan perubahan warna dari kuning ke merah. Hasil analisa dengan spektrofotometer UV-Vis reseptor memberikan perubahan panjang gelombang dari 395 nm menjadi 472 nm pada penambahan anion sianida. Reseptor (E)-4-((2-(2,4-dinitrophenyl)hydrazineylidene)methyl)-2-methoxyphenol dapat mendeteksi anion CN- dengan limit deteksi sebesar 7 mM. A Hydrazone Compound from Vanillin-DNPH as Colorimetric Sensor of Cyanide Anion. A hydrazone compound (E)-4-((2-(2,4-dinitrophenyl)hydrazineylidene)methyl)-2-methoxyphenol has been synthesized from vanillin and 2,4-dinitrophenylhydrazine (DNPH). The anion sensor study were done by adding Br-, CN-, F-, SO42-, Cl-, I- , CO32-, CH3COO- and H2PO4- anion in acetonitrile solvent. The detection limit study of receptor E)-4-((2-(2,4-dinitrophenyl)hydrazineylidene)methyl)-2-methoxyphenol for cyanide anion was carried out in acetonitrile. The result of anion sensor study shows that the receptor was selective to cyanide anion by providing change of color from yellow to red. The analysis result using spectrophotometer ultraviolet-visible of the receptor provided change of maximum wavelength from 395 nm to 472 nm when the cyanide anion was added. Receptor (E)-4-((2-(2,4-dinitrophenyl) hydrazineylidene)methyl)-2-methoxyphenol can detect CN- with limit of detection 7 mM.